2021
DOI: 10.1039/d1qi00995h
|View full text |Cite
|
Sign up to set email alerts
|

CsPbBr3 and CsPbI3 rhombic dodecahedra and nanocubes displaying facet-dependent optical properties

Abstract: CsPbBr3 rhombic dodecahedra, octahedra, and nanocubes have been synthesized using typical reagents but by adjusting the amounts of organic capping molecules used and the reaction temperature. Although some Cs4PbBr6 has...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…39,40 Especially the substitution of the volatile methylammonium (MA + ) by inorganic cations plays an important role, also regarding facet dependent properties. 41 The substituent that has attracted the most interest is Cesium, as its radius (r(Cs + ) = 167 pm) fits best into the perovskite structure of the lead halide and the mixed materials show higher stability against elevated temperatures. 42,43 Furthermore, Premkumar et al have shown that the integration of Cs + not only enhances the stability of the perovskite materials, they also proven the enhanced PL intensity by the reduction of non-radiative recombination related to pure MAP-bBr3.…”
Section: Resultsmentioning
confidence: 99%
“…39,40 Especially the substitution of the volatile methylammonium (MA + ) by inorganic cations plays an important role, also regarding facet dependent properties. 41 The substituent that has attracted the most interest is Cesium, as its radius (r(Cs + ) = 167 pm) fits best into the perovskite structure of the lead halide and the mixed materials show higher stability against elevated temperatures. 42,43 Furthermore, Premkumar et al have shown that the integration of Cs + not only enhances the stability of the perovskite materials, they also proven the enhanced PL intensity by the reduction of non-radiative recombination related to pure MAP-bBr3.…”
Section: Resultsmentioning
confidence: 99%
“…For light-emitting CsPbBr 3 and CsPbI 3 perovskite nanocrystals, optical size and facet effects are also observable. [62,63] The much bigger CsPbBr 3 and CsPbI 3 rhombic dodecahedra actually show more blue-shifted absorption and emission bands than those of their 10 nm nanocubes, demonstrating the exceptionally large optical facet influence. For CsPbCl 3 cubes and edge-truncated cuboids with broad size distributions, their band gaps can be very similar as optical size and facet effects are mixed.…”
Section: Size-and Facet-dependent Optical Propertiesmentioning
confidence: 99%
“…[21][22][23][24][25] This surface layer naturally accounts for the observation of facet-related absorption and emission band shifts in various semiconductor nanocrystals including Cu 2 O, SrTiO 3 , CsPbX 3 and Ag 2 O. 2,19,[26][27][28][29] In addition to the optical facet effect, the absorption band, and hence band gap, can shift continuously from quantum nanostructures to very large particles. [30][31][32] Because these semiconductor facet-dependent properties are interesting and potentially useful, as demonstrated in Cu 2 O-Si wafer heterostructures for current rectification, 33 it is desirable to explore the growth of other polyhedral inorganic crystals such as cadmium oxide to broaden the scope of investigation.…”
Section: Introductionmentioning
confidence: 99%